Contribuições de Edith de Magalhães Fraenkel na construção da enfermagem brasileira - Prochera, Madalena Cristina (2025)
The life of Edith de Magalhães Fraenkel (1889-1969) can be considered a reflection of Brazilian nursing at the beginning of the 20th century and, to some degree, of today’s nursing as well, for this hard-working, dedicated nurse was both a well-meaning entrepreneur in the health field and, at the same time, a hostage to a system. To carry out this research, we drew on material from bibliographical surveys and, primarily, from two original documents: Annais de Enfermagem, published in May 1932 and October 1934. In these, E. Fraenkel describes her purpose and how nursing was being developed. In this study, it has been possible to develop a critical analysis, not of Fraenkel's work in itself, but of its relationship with the dominant influences affecting medical science at that time, specifically that the paradigm of illness was apparently placed in focus in a somewhat complex way. It is thus possible to see that we are experiencing today the consequences of a previous period, which is being reflected in our current generation of nurses. Visiting the past therefore raises questions about the true purpose of Nursing